The Effects of Social Media on Consumer Buying Behavior Among Adolescents in Hawaii - Lim, Vivienne (Digital Repository of Theses - SSBM Geneva, 2025)
Social media platforms have significantly improved communication, interaction and obtaining information, and massive popularity (Daniels et al., 2021). Adolescents have contributed to making social media a daily routine and socialization. Marketers have become aware of the possibility of impacting purchasing habits of this demographic because of their changing behavior. The main objective of this research is to investigate how the use of social media affects the purchasing patterns and choices of adolescents residing in Hawaii. There are multiple reasons why examining the correlation between social media and the actions of young consumers is tremendously significant (Dedoncker & McLean, 2022). First, teenagers constitute a crucial group of customers with distinctive requirements, likings, and buying behavior (He, 2022). Marketers and businesses operating in Hawaii can gain valuable insights by comprehending the impact of social media on individuals' decisionmaking processes. Additionally, Hawaii presents a unique environment, characterized by its singular cultural background and geographic remoteness, that lends itself to analyzing how social media influences consumer actions among a particular populace (Nofal et al., 2020). This study aims to enhance understanding of marketing and social media disciplines. At the same time, we intend to aid the local community by delivering practical recommendations for enterprises based in Hawaii.